ANALYSIS OF HALAL TOURISM CONCEPTS IN WEST SUMATERA (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2019)
This study analyzes the influence of the tourism sector rearrangement (X1) and social media promotion (X2) on the resident’s economy (X3) in supporting the concept of halal tourism in West Sumatra. From the research that has been done shows that a significant difference between the rearrangement of the tourism sector on the resident’s economy by 59.0% and contained a less significant influence between social media promotion and population to influence the economy by 27.7%, while there are significant together is rearrangement of the tourism sector (X1) and social media promotion (X2) on the resident’s economy (X3) with f calculated at 79.8255.